Integration of mRNA and microRNA analysis reveals the molecular mechanisms underlying drought stress tolerance in maize (Zea mays L.) - Jiao, Peng; Ma, Ruiqi; Wang, Chunlai; Chen, Nannan; Liu, Siyan; Qu, Jing; Guan, Shuyan; Ma, Yiyong (Frontiers in Plant Science, 2022)
Drought is among the most serious environmental issue globally, and seriously affects the development, growth, and yield of crops. Maize (Zea mays L.), an important crop and industrial raw material, is planted on a large scale worldwide and drought can lead to large-scale reductions in maize corn production; however, few studies have focused on the maize root system mechanisms underlying drought resistance. In this study, miRNA–mRNA analysis was performed to deeply analyze the molecular mechanisms involved in drought response in the maize root system under drought stress. Furthermore, preliminary investigation of the biological function of miR408a in the maize root system was also conducted. The morphological, physiological, and transcriptomic changes in the maize variety “M8186” at the seedling stage under 12% PEG 6000 drought treatment (0, 7, and 24 h) were analyzed. With prolonged drought stress, seedlings gradually withered, the root system grew significantly, and abscisic acid, brassinolide, lignin, glutathione, and trehalose content in the root system gradually increased. Furthermore, peroxidase activity increased, while gibberellic acid and jasmonic acid gradually decreased. Moreover, 32 differentially expressed miRNAs (DEMIRs), namely, 25 known miRNAs and 7 new miRNAs, and 3,765 differentially expressed mRNAs (DEMRs), were identified in maize root under drought stress by miRNA-seq and mRNA-seq analysis, respectively. Through combined miRNA–mRNA analysis, 16 miRNA–target gene pairs, comprising 9 DEMIRs and 15 DEMRs, were obtained. In addition, four metabolic pathways, namely, “plant hormone signal transduction”, “phenylpropane biosynthesis”, “glutathione metabolism”, and “starch and sucrose metabolism”, were predicted to have important roles in the response of the maize root system to drought. MiRNA and mRNA expression results were verified by real-time quantitative PCR. Finally, miR408a was selected for functional analysis and demonstrated to be a negative regulator of drought response, mainly through regulation of reactive oxygen species accumulation in the maize root system. This study helps to elaborate the regulatory response mechanisms of the maize root system under drought stress and predicts the biological functions of candidate miRNAs and mRNAs, providing strategies for subsequent mining for, and biological breeding to select for, drought-responsive genes in the maize root system.